2005
DOI: 10.1002/ijc.20888
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase polymorphisms and risk of squamous cell carcinoma of the head and neck: A case‐control analysis

Abstract: Folate deficiency is implicated in cancer risk that may be modulated by a genetic variation in the methylenetetrahydrofolate reductase (MTHFR) gene in folate metabolism. We hypothesized that genetic variants in MTHFR are associated with risk of squamous cell carcinoma of the head and neck (SCCHN). We genotyped 3 MTHFR polymorphisms (C677T, A1298C and G1793A) and estimated their haplotypes in a hospital-based case-control study of 537 SCCHN cases and 545 cancer-free controls. The controls were frequency-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 42 publications
6
43
1
Order By: Relevance
“…We found no increase in risk associated with the variant genotypes, a result consistent with our previous study of squamous cell carcinoma of the head and neck (49). The newly identified G1793A located in exon 11 at codon 594, causes an arginine-to-glutamine change (28).…”
Section: Discussionsupporting
confidence: 92%
“…We found no increase in risk associated with the variant genotypes, a result consistent with our previous study of squamous cell carcinoma of the head and neck (49). The newly identified G1793A located in exon 11 at codon 594, causes an arginine-to-glutamine change (28).…”
Section: Discussionsupporting
confidence: 92%
“…Given the relationship between MTHFR function and levels of circulating folate (in the form of 5-methyl-THF), this is to be expected, particularly because various MTHFR polymorphisms have been implicated as risk factors for HNSCC (49). Preliminary analysis of our data has suggested that MTHFR 677genotype is not an independent risk factor for HNSCC, but its influence on hypomethylation may suggest the possibility for effect modification by this or other factors.…”
Section: Discussionmentioning
confidence: 75%
“…Univariate and multivariate unconditional logistic regression analyses were used to calculate odds ratios (ORs) and their 95% confidence intervals (CIs) for assessing risk of lung cancer. The putative risk genotypes and alleles were determined, if their frequencies were higher in the lung cancer patients than in the controls [18]. Because there was no prior information about the effects of these SNPs on lung cancer risk, we used Akaike's information criterion (AIC) to select the best genetic-effect model for each SNP.…”
Section: Discussionmentioning
confidence: 99%